OPTIMIZATION EXTRACT OF NUTMEG FLESH (MYRISTICA FRAGRANS) NANOEMULSION SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) USING D-OPTIMAL MIXTURE DESIGN METHOD AS AN ANTI-INFLAMMATORY ACTIVITY - Made Dwike Swari Santi; Ni Wayan Rika Kumara Dewi; Maureen Vianney (Meditory : The Journal of Medical Laboratory, 2026)
Background: Nutmeg flesh (Myristica fragrans), known to contain flavonoid compounds with anti-inflammatory activity. Extract of nutmeg flesh can be formulated into nanoemulsion using the SNEDDS technique represents an innovative drug delivery method that enhances drug absorption in the body.Objective: This study aimed to determine the optimal formulation extract of nutmeg flesh (Myristica fragrans) nanoemulsion preparation using the SNEDDS technique as an anti-inflammatory.Methods: This research employs an experimental design, with data collection carried out through observation and measurement scales. Observations are conducted on the evaluation of the physical quality of the nanoemulsion formulation, as well as on the anti-inflammatory activity test using male white mice (Mus musculus).Results: The analytical findings confirmed the presence of flavonoids as secondary metabolites in nutmeg extract. The optimal formula consisted of VCO (11%), Tween 80 (73%), and PEG 400 (15%), with predicted values of viscosity at 347 mPas, transmittance at 97.8%, emulsification time of 5 seconds, and a desirability value of 1. The anti-inflammatory activity, based on the percentage of inhibition, showed a high result in the SNEDDS test group, with an inhibition rate of 90%.Conclusions: Our study revealed that the SNEDDS extract of nutmeg flesh contains secondary metabolites and exhibits strong anti-inflammatory activity.